Revealing Millennials’ Networks in Discussing Maritime Issues within the Triple Helix of University-Industry-Government - Tatak Setiadi (Center for Southeast Asian Social Studies (CESASS), 2021)
Millennials' networks within the triple helix of University-Industry-Government show unusual communication structures and are challenging to be revealed. Using the direct and online written interview with the millennials found about 817 relations (edges) to 347 actors (nodes) in total. Analysis by Social Network Analysis (SNA) found: (1) the dominant issues of the maritime human resources are about future work prospects and specialties field, imbalance of supply and demand of maritime human resources, and improvement needed of industry's human resources (2) the dominant skill issue is capacity building and continuous learning, (3) the highest degree of centrality and closeness centrality has resulted from Industry, (4) the highest betweenness centrality and eigenvector centrality has resulted from University, (5) there is moderate positive correlation of ages to closeness centrality and weak negative correlation to eigenvector centrality, (6) there is a moderate positive correlation of education levels to closeness centrality, (7) there is a weak negative correlation of gender to eigenvector centrality, and (8) there is a statist relation of the triple helix in discussing maritime issues.